Cruz, esquadro, compasso e quadro-negro : uma história do Instituto Anglicano Barão do Rio Branco - Erechim/RS - Drey, Vinícius (2013)
This dissertation was presented to the University of Passo Fundo Post Graduate Program in Education, in the research field of educational policies, is inserted in the historical field of the Brazilian educational institutions. The main topic is the analysis of elements of the history of largest Anglican Educational institution in Latin America today, the Anglican Institute Barão do Rio Branco (IABRB), located in Erechim, in the northern part of Rio Grande do Sul. The studied period of time is from its founding (1929) until the moment it came to be administered by its own maintaining institution (1953). The main objective of this research is to analyze the context of the appearance of the Anglican school, its proposal for differentiated education, influenced by positivist thinking and Free Masons, which contrasted with the traditional pedagogy disseminated by the Roman Catholic confessional schools. The creation of a school with innovative proposals for the municipality, was aligned with interests of science oriented local political leaders with a strong regional influence of Freemasonry. The guiding question of the research is how was it possible to create a school with a Protestant denominational profile and lay background and ideology, within a religious-educational context profoundly marked by the Roman Catholic religion? In its methodology, this work embraces a proposed dialectical reconstruction of regional history in which the school is located. As research resources were utilized documents found at the Anglican school and parish at Erechim, the journal Estandarte Cristão which circulates internally in The Episcopal Anglican Church of Brazil, and the Synods Reports from the Anglican Clergy and Laity. The dissertation is structured in three chapters, the first being a reconstruction of the local context, where and when the Anglican missionaries began their activities, whom were purposely located along the north trunk railway, connecting the Rio Grande do Sul to São Paulo. The second chapter is a theoretical, historical and bibliographical review of Anglicanism, Freemasonry and Positivism, because they were in some way responsible for and influenced the creation of the school in Erechim, with an institutional and pedagogical distinctive and innovative proposal for the Upper Uruguay River region in the first half of the twentieth century. In the third and final chapter, this work reveals the connection between Freemasonry and the implementation of a school based on secular principles, with support and encouragement from the local elite, who saw the founding of IABRB the prerogative to become an alternative to denominational Roman Catholic schools, that then favored a traditional and conservative pedagogy, and also denied the advances of scientific thought. This work also analyzes the discourse of the Anglican clergy, regarding some liberal and progressive matters, for the context of the era, and unveiled part of Masonic symbolism present in various elements of school´s everyday life. The main contribution of this research lies on the analysis of an educational institution that plays such an important role in the northern region of Rio Grande do Sul, and on the historical reconstruction of this educational institution in order to establish the relationship between a (Anglican) religious institution, Freemasonry and Positivism. What these three different traditions have in common is the foundation of a school rooted on the ideas of secularism and scientific thought. In this sense, the research contributes to think about educational policies in the early decades of the twentieth century in a particular context articulated with international organizations such as the Freemasons